An online diabetes nutrition education programme for American Indian and Alaska Native adults with type 2 diabetes: perspectives from key stakeholders. Issue 6 (17th April 2021) - Stotz, Sarah; Brega, Angela G; Lockhart, Steven; Hebert, Luciana E; Henderson, J Neil; Roubideaux, Yvette; Moore, Kelly
Abstract: Objective: To explore stakeholder perspectives regarding online diabetes nutrition education for American Indians and Alaska Natives (AI/AN) with type 2 diabetes (T2D). Design: Qualitative data were collected through focus groups and interviews. Focus group participants completed a brief demographic and internet use survey. Setting: Focus groups and community participant interviews were conducted in diverse AI/AN communities. Interviews with nationally recognised content experts were held via teleconference. Participants: Eight focus groups were conducted with AI/AN adults with T2D ( n 29) and their family members ( n 22). Community participant interviews were conducted with eleven clinicians and healthcare administrators working in Native communities. Interviews with nine content experts included clinicians and researchers serving AI/AN. Results: Qualitative content analysis used constant comparative method for coding and generating themes across transcripts. Descriptive statistics were computed from surveys. AI/AN adults access the internet primarily through smartphones, use the internet for many purposes and identify opportunities for online diabetes nutrition education. Conclusions: Online diabetes nutrition education may be feasible in Indian Country. These findings will inform the development of an eLearning diabetes nutrition education programme for AI/AN adults with T2D.